Bond-shear Behavior of FRP Rods as a Function of Attachment Configuration - Agung Budipriyanto; Ay Lie Han; Hsuan Teh Hu (JACEE (Journal of Advanced Civil and Environmental Engineering), 2018)
The use of external reinforcement to improve or enhances the flexural capacity of a member depends on the transfer capacity, and the failure behavior of the composite between the reinforcement, the epoxy resin and the concrete. The most influencing factor is the bond-shear capacity between the rod and the epoxy, and the epoxy to the concrete. Fiber Reinforced Polymer (FRP) rods are the latest alternate for fulfilling the external reinforcement scheme. In the field, the mandated embedment depth as outlined by the ACI 440 code, could customary not be achieved since factors such as the depth of the concrete cover, and presence of stirrups limits the space. This study is aimed to evaluate the effect of FRP rod configurations with respect to the concrete surface, to the effectiveness of external reinforcement. The study looked into the bond-shear capacity as well as the mode of failure, influence by the rod attachment depth. It was shown that the embedment depth significantly influenced the failure mode, and therefore the strain transfer capacity from the concrete to the rods.